PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DAN PEMANFAATAN MEDIA PROMOSI PADA UMKM AHYA FOOD DAN AQILA SNACK - Astuti, Linda Tri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service program aims to enhance the financial management skills of MSME actors and their ability to utilize digital promotion strategies. The activity was conducted in response to the low awareness of simple financial reporting and the limited use of digital promotional media among business owners. Assistance was provided to two partners, Ahya Food and Aqila Snack, through initial interviews, educational sessions, financial record-keeping practice, and training on WhatsApp Business and promotional banner design. The results indicate significant improvements in partners’ ability to record transactions systematically and use WhatsApp Business as a communication and promotional tool. Partners also gained a better understanding of the role of visual media, such as banners, in strengthening brand identity and attracting customers. Overall, the program contributed positively to improving professionalism, promotional efficiency, and the competitiveness of MSMEs. These findings highlight that structured assistance can strengthen the independence and sustainability of small businesses in the community.